The Administrative Role of Principals: Insights and Implication in Secondary Schools Mardan District (Journal of Social Sciences Review, 2021)
Secondary schools are educational facilities entrusted with preparing pupils for higher education and professional training. Principals are the major stakeholders entrusted with administrative responsibilities in secondary schools to satisfy society's needs and deliver excellent education to pupils. The research aims to analyze the administrative function of principals in secondary schools in Mardan district, Khyber Pakhtunkhwa, Pakistan, in light of their organizational role at the secondary level. The study's aims were to examine at the administrative position of secondary school administrators and offer techniques for more successful secondary school administration. The investigation comprised 100 government male high school administrators from the Mardan area. A dependable instrument was created, verified, and pilot tested. The information was acquired using a unique administration instrument and assessed using mean scores, standard deviation, and the chi-square test. The research revealed that principals have a predominantly administrative job in high school management. They develop the school's vision and mission, provided school facilities, organize the teaching-learning process, plan co-curricular activities, supervise school activities, identify students' needs and demands, maintain the school's records, ensure financial management, collaborate with parents and society, coordinate with educational authorities, track, and evaluate the school's activities. For successful secondary school administration, the research advised offering teaching for incoming principals at the time of admission and capacity development for present principals in financial management, record keeping, staff management, service law, and ICT skills.Keywords: administrative role, Mardan, Pakistan, principals, secondary schools
Keywords: administrative role, Pakistan, principals, secondary schools